Further reply to remarks of R Cross on 'A comparative study of two types of ball-on-ball collision'. (12th January 2018) - White, Colin
Abstract: In this letter, I show how a perceived approximation error in my first letter, White (2017 Phys. Ed .53 016502) concerning my explanation of the dynamic motion of two interacting Newtons Cradle balls, proves to me insignificant. Although these second and third order errors described are shown to be minimal, they do raise the opportunity to discuss the precise and more intricate ball interactions in finer detail.